Inactivation of GDP‐fucose transporter gene (Slc35c1) in CHO cells by ZFNs, TALENs and CRISPR‐Cas9 for production of fucose‐free antibodies. Issue 3 (11th December 2015) - Chan, Kah Fai; Shahreel, Wahyu; Wan, Corrine; Teo, Gavin; Hayati, Noor; Tay, Shi Jie; Tong, Wen Han; Yang, Yuansheng; Rudd, Pauline M.; Zhang, Peiqing; Song, Zhiwei
Abstract: Removal of core fucose from N ‐glycans attached to human IgG1 significantly enhances its affinity for the receptor FcγRIII and thereby dramatically improves its antibody‐dependent cellular cytotoxicity activity. While previous works have shown that inactivation of fucosyltransferase 8 results in mutants capable of producing fucose‐free antibodies, we report here the use of genome editing techniques, namely ZFNs, TALENs and the CRISPR‐Cas9, to inactivate the GDP‐fucose transporter (SLC35C1) in Chinese hamster ovary (CHO) cells. A FACS approach coupled with a fucose‐specific lectin was developed to rapidly isolate SLC35C1‐deficient cells. Mass spectrometry analysis showed that both EPO‐Fc produced in mutants arising from CHO‐K1 and anti‐Her2 antibody produced in mutants arising from a pre‐existing antibody‐producing CHO‐HER line lacked core fucose. Lack of functional SLC35C1 in these cells does not affect cell growth or antibody productivity. Our data demonstrate that inactivating Slc35c1 gene represents an alternative approach to generate CHO cells for production of fucose‐free antibodies. Abstract : GDP‐fucose is synthesized in the cytosol and has to be transported into the Golgi to serve as the substrate for fucosylation reactions. The GDP‐fucose transporter (SLC35C1) is a dimeric antiporter. It transports one GMP molecule out of the Golgi for each GDP‐fucose molecule it transports into the Golgi. The fucose residue is then transferred from GDP‐fucose to the core position on the N ‐glycans by FUT8. The authors have inactivated the Slc35C1 gene in CHO cells using ZFNs, TALENs and the CRISPR‐Cas9. The mutants are named CHO‐gmt3 cells and have been used to produce fucose‐free antibodies.